PERANAN SLOGAN ANTI KORUPSI TERHADAP PENCEGAHAN KORUPSI (Studi Kasus Kantor BPN Kota Medan) - Ismail Fahmi (PERSPEKTIF, 2013)
The Indonesian people who are active in implementing reforms in dire need of development of a condition that can support the creation of the national development goals of a just and prosperous society based on Pancasila. Upholding the rule of law is a necessary condition for the survival and the success of the implementation of national development. corruption that is around us, there at home, school, community, and the highest government and in government. Those who commit petty corruption sometimes considers what he does. This is very worrying, because after all, if an organization is built of corruption will be harmful to the joints of justice in society. See the phenomenon of corruption in Indonesian Corruption Eradication Commission (KPK), made some slogan that describes the threat of corruption act as if on display at the Land Town. For that in doing research on “MESAGGE ROLE OF PREVENTION CONFICT CORRUPTION (A CASE STUDY OF CITY FIELD OFFICE BPN)". The results of this study found that the anti-corruption mesagge give effect to the service stations do not open public corruption and a large partly have the courage to explain to the officer not to do corruption.